Cardiac telocytes are double positive for CD34/PDGFR‐α. Issue 8 (17th June 2015) - Zhou, Qiulian; Wei, Lei; Zhong, Chongjun; Fu, Siyi; Bei, Yihua; Huică, Radu‐Ionuț; Wang, Fei; Xiao, Junjie
Abstract Telocytes (TCs) are a distinct type of interstitial cells, which are featured with a small cellular body and long and thin elongations called telopodes (Tps). TCs have been widely identified in lots of tissues and organs including heart. Double staining for CD34/PDGFR‐β (Platelet‐derived growth factor receptor β) or CD34/Vimentin is considered to be critical for TC phenotyping. It has recently been proposed that CD34/PDGFR‐α (Platelet‐derived growth factor receptor α) is actually a specific marker for TCs including cardiac TCs although the direct evidence is still lacking. Here, we showed that cardiac TCs were double positive for CD34/PDGFR‐α in primary culture. CD34/PDGFR‐α positive cells (putative cardiac TCs) also existed in mice ventricle and human cardiac valves including mitral valve, tricuspid valve and aortic valve. Over 87% of cells in a TC‐enriched culture of rat cardiac interstitial cells were positive for PDGFR‐α, while CD34/PDGFR‐α double positive cells accounted for 30.25% of the whole cell population. We show that cardiac TCs are double positive for CD34/PDGFR‐α. Better understanding of the immunocytochemical phenotypes of cardiac TCs might help using cardiac TCs as a novel source in cardiac repair.